anonymous
  • anonymous
log6 (x+4) - log6 (x-2)= log6 (x)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
\[\log_{6} (x+4) - \log_{6} (x-2= \log_{6} (x+4)/(x-2) = \log_{6} x\] then take exponential (base 6 ofcource) bouth sides and solve equation
anonymous
  • anonymous
i dont understand how you get x from that
anonymous
  • anonymous
taking exponential \[6^{\log 6 (x+4)/(x−2)}= 6^{\log 6 x}\] (x+4)/(x-2) =x x+4 = x(x-2) and solve

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
you should get x=4 and x=-1
anonymous
  • anonymous
how does x(x-2) equal out to -1?
anonymous
  • anonymous
\[x^{2} -3x -4 =0\]
anonymous
  • anonymous
ohh. alright thanks. i understand now
anonymous
  • anonymous
this is what u get if u pass all terms to one side x+4 = x(x-2)
anonymous
  • anonymous
thank you, can you help me with some other problems on my profile?
Directrix
  • Directrix
log6 (x + 4) - log6(x-2) = log6(x) log6 [ (x + 4) / (x + 2) ] = log6(x) [ (x + 4) / (x + 2) ] = x x^2 - 2x = x + 4 x^2 - 3x - 4 = 0 (x - 4) (x + 1) = 0 x = 4 or x = -1 x = 4 (x = -1 is an extraneous solution)

Looking for something else?

Not the answer you are looking for? Search for more explanations.